2013
DOI: 10.1002/ptr.5031
|View full text |Cite
|
Sign up to set email alerts
|

Salvia MiltiorrhizaInduces VEGF Expression and Regulates Expression of VEGF Receptors in Osteoblastic Cells

Abstract: This study investigated in vitro whether Salvia Miltiorrhiza Bunge (SM) induces vascular endothelial growth factor (VEGF) expression and regulates expression of VEGF receptors 1 (VEGFR-1) and 2 (VEGFR-2) on osteoblasts. MC3T3-E1 cells were cultured with SM and VEGF at points 24, 48 and 72 h. A blank control was included. The mRNA expression of VEGF, VEGFR-1 and VEGFR-2 was examined using real-time polymerase chain reaction. VEGF protein expression was examined using enzyme linked immunosorbent assay. SM increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For bone formation, ALP, OPN and OCN were found increasing at different phases of intervention [8,20]. The process of osteogenesis consists of cell proliferation, cell differentiation, and mineralization, and ALP, OPN and OCN are related to the different stages of this process: ALP is an early marker, which is known to be responsible for osteoblastic differentiation; while OPN and OCN are regarded as late markers, as OPN is a major non-collagenous bone matrix protein secreted into the mineralizing extracellular matrix, and OCN is also closely related to calcification [17][18][19].…”
Section: Dynamic Balance Of Bone Remodelingmentioning
confidence: 98%
See 2 more Smart Citations
“…For bone formation, ALP, OPN and OCN were found increasing at different phases of intervention [8,20]. The process of osteogenesis consists of cell proliferation, cell differentiation, and mineralization, and ALP, OPN and OCN are related to the different stages of this process: ALP is an early marker, which is known to be responsible for osteoblastic differentiation; while OPN and OCN are regarded as late markers, as OPN is a major non-collagenous bone matrix protein secreted into the mineralizing extracellular matrix, and OCN is also closely related to calcification [17][18][19].…”
Section: Dynamic Balance Of Bone Remodelingmentioning
confidence: 98%
“…OCN is closely related to calcification [19]. [8,20] It was found that the mRNA expression of ALP increased by 73% after VEGF incubation for 24 hrs (p<0.001), but reduced by 14% and 41% at 48 hrs (p<0.001) and 72 hrs (p<0.05) respectively when compared to the control [8]. For the other two factors, OPN expression decreased by 11% (p<0.001) and OCN dropped by 41% (p<0.001) at 24 hrs; both the expression of OPN and OCN did not show any change at 48 hrs; but at 72hrs, OPN increased by 94% (p<0.001) and OCN grew by 149% (p<0.001) [8,20].…”
Section: Bone Formationmentioning
confidence: 99%
See 1 more Smart Citation